Histopathological study of ovarian lesions in a tertiary care center in Hyderabad, India: a retrospective five-year study - Prakash, Akina; Chinthakindi, Sravan; Duraiswami, Ramanan; V., Indira (International Journal of Advances in Medicine, 2017)
Background: The aim of the study was to identify the pattern of pathologies involving ovarian mass lesions which were received for histopathological evaluation at a tertiary hospital in Hyderabad, Telangana, India during the period January 2012 to December 2016. Methods: The data pertaining to samples of ovarian lesions received for histopathological evaluation at the laboratory of a tertiary care hospital in Hyderabad from January 2012 to December 2016, were analyzed to determine the pattern of pathologies diagnosed during such evaluation and the age distribution of all lesions. Results: Non-neoplastic lesions of the ovary constituted 44.0% of all cases received; follicular cysts constituted 45.5% of these lesions. Malignant lesions constituted only 2.0% of all pathologies. Serous cystadenoma of the ovary constituted the predominant neoplastic lesion diagnosed (62.5% of all neoplastic lesions). 53.2% of patients whose samples were received belonged to the age group of 20-39 years. 90.8% of the lesions were unilateral Conclusions: The majority of ovarian lesions received for evaluation were benign and unilateral. Most patients were in the third to sixth decades of life.